Optimal Utilization of Hydro-Energetic Potential of Flows on Moraca River - Mitrović, Ratko (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
The process of finding optimal solution for utilization of hydro-energetic potential of a river flow is a very complex procedure, because it is necessary to find a compromise between an energetically optimal solution and a solution with lower negative influence on the environment and sociological conditions, which is often contradictory in practice. In order to show more precisely the complexity in choosing an optimal solution for utilization of hydro-energetic potential of a river flow, a mathematical model of multi-criteria optimization and multi-criteria rating for different variants of utilization of the River Moraca basin is posited. For the process of multi-criteria optimization, a complete software packages and large documentation as well as preliminary projects for planned hydropower plants have been used. The aim is to reach an optimal utilization of hydro-energetic potential of a river flow, especially in cases when the existing investigations do not give priority to a particular variant, and the hydropower plants has to be constructed in near future. DOI: http://dx.doi.org/10.3126/hn.v8i0.4927 Hydro Nepal: Journal of Water, Energy and Environment Issue No. 8, 2011 January Page: 61-68 Uploaded date: 23 June, 2011